2011
DOI: 10.1002/cne.22663
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of vesicular glutamate transporter 2 (vGluT2) in the central nervous system of the pigeon (Columba livia)

Abstract: Glutamatergic neurons are distributed widely in the telencephalic pallium of birds, but their targets are unknown. In the present study, a polyclonal antibody was produced against pigeon vesicular glutamate transporter 2 (vGluT2) and was used for Western blot and immunohistochemistry to detect projection targets of glutamatergic neurons in the pigeon central nervous system. The molecular weight of vGluT2 was measured at 65 kDa. vGluT2 immunoreactivity was observed in neuropil, but not in neuronal cell bodies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 51 publications
(87 reference statements)
4
31
0
Order By: Relevance
“…In situ hybridization studies using a vGluT2 probe morphologically demonstrated the presence of a large number of glutamatergic neurons in HF of pigeons and zebra finches, especially apparent in neurons of the V‐shaped layer (Islam and Atoji, ; Karim et al, ; present study). Immunohistochemically, vGluT2 protein has been ultrastrucutrally demonstrated to be localized in presynaptic boutons of asymmetric synapses in the pigeon brain (Atoji, ). Considering the localization of zinc‐containing presynaptic boutons described above, vGluT2 probably colocalizes in zinc‐containing axon terminals.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization studies using a vGluT2 probe morphologically demonstrated the presence of a large number of glutamatergic neurons in HF of pigeons and zebra finches, especially apparent in neurons of the V‐shaped layer (Islam and Atoji, ; Karim et al, ; present study). Immunohistochemically, vGluT2 protein has been ultrastrucutrally demonstrated to be localized in presynaptic boutons of asymmetric synapses in the pigeon brain (Atoji, ). Considering the localization of zinc‐containing presynaptic boutons described above, vGluT2 probably colocalizes in zinc‐containing axon terminals.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of GluA1 neurons in the optic tectum largely overlaps with that of vGluT2 immunoreactive axon terminals (Atoji, 2011). In contrast, the dorsal thalamic region weakly expresses GluA2 mRNA but not GluA1 mRNA (Ottiger et al, 1995;Islam and Atoji, 2008), but the thalamic region revealed intense vGluT2 immunoreactivity (Atoji, 2011). The difference of mRNA expression of GluA1 and GluA2 between the optic tectum and dorsal thalamic nuclei is unknown.…”
Section: Discussionmentioning
confidence: 95%
“…GluA1 is immunohistochemically localized in neurons of layers 2e7, 9, and 10 in the pigeon optic tectum (Theiss et al, 1998). The localization of GluA1 neurons in the optic tectum largely overlaps with that of vGluT2 immunoreactive axon terminals (Atoji, 2011). In contrast, the dorsal thalamic region weakly expresses GluA2 mRNA but not GluA1 mRNA (Ottiger et al, 1995;Islam and Atoji, 2008), but the thalamic region revealed intense vGluT2 immunoreactivity (Atoji, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The GLv, LM, and GT receive topographic retinal projections from different retinal ganglion cell populations (Crossland and Uchwat, ; Gamlin and Cohen, ; Wylie et al, ), which may release glutamate in all these structures (Guo et al, ; Atoji, ). At the same time, AMPA receptors GluR1, GluR2/3, and GluR4 are expressed in the GT, LM, and GLv (Pires and Britto, ).…”
Section: Discussionmentioning
confidence: 99%